SINONIM KATA JAMAL DALAM KAMUS AL-MUNAWWIR ARAB-INDONESIA - Yusnindar Abd Gani; Sugeng Sugiyono (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2017)
This study aims to find out the words that are synonymous with the word jamal 'camels' in the dictionary of Al-Munawwir Arab Indonesia. In addition to know the form of categories of meaning of words that are synonymous with the word jamal 'camels' in terms of semantic fields and components of meaning. The method used in this study is descriptive method and this research is included in the type of library research (Library research), research conducted solely based on facts or phenomena that exist, by identifying the problems contained in the primary data ie Dictionary Al-Munawwir Arab-Indonesia, then collects and describes words related to the synonyms of the word 'camels' in the dictionary by providing an analysis of the available data.The results of this study are the authors found about 144 words that are synonymous with the word jamal 'camels' in Al-Munawwir Arab-Indonesia Dictionary and also produce as many as 55 (fifty five) different components of meaning. In addition the authors classify the synonyms of the word jamal 'camels' in several categories, of which are based on the character and physical condition of the 'camel' clock, then based on the activities and equipment of the camel 'clock', also based on the age of the 'camel' ', And last based on the number of' camel 'hours. The author also analyzes the semantic field by using paradigmatic analysis which is then generated by several words, including al-ibil, an-nāqah, and al-baῑru. And the author also finds the opposite word (antonym) with the word 'camel', from these anonymous words found two types of anthons, the first is binary opposition, the second graded antonym is a tiered or gradable resistance Opposite). The authors conclude that no synonyms are comprehensive (total) because the whole synonym is never encountered. Even if the synonymous words have a meaning equation. Because each word will be different meaning if used in different situations.